Structural And Functional Identification Of The Smart Marketing System Model In The Service Sector - Raximov Anvar Norimovich; Jurayev Farrux Dustmirzayevich; Rahimov Abdihakim Muhammadiyevich (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This article describes the structural and functional aspects of the smart marketing system. In the context of our study, the structure of the smart management system comprises the smart dispatcher service, the operations of service providers, the smart information system, while the smart performance mechanism includes the smart dispatcher service, the operations of service providers and the smart performer. The model of the smart marketing system for online public food services is based on the structural composition of two subsystems, six functional, and two auxiliary intermediary blocks. The functionality of the structural blocks of the smart marketing system model for public food online services is explained.